2017
DOI: 10.2196/humanfactors.8117
|View full text |Cite
|
Sign up to set email alerts
|

An eHealth Application of Self-Reported Sports-Related Injuries and Illnesses in Paralympic Sport: Pilot Feasibility and Usability Study

Abstract: BackgroundSport participation is associated with a risk of sports-related injuries and illnesses, and Paralympic athletes’ additional medical issues can be a challenge to health care providers and medical staff. However, few prospective studies have assessed sports-related injuries and illnesses in Paralympic sport (SRIIPS) over time. Advances in mobile phone technology and networking systems offer novel opportunities to develop innovative eHealth applications for collection of athletes’ self-reports. Using eH… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 38 publications
4
30
0
Order By: Relevance
“…The study is part of SRIIPSS, which is a prospective (1‐year) longitudinal study of self‐reported SRIIPS . The eHealth application used for data collection has previously been described and tested in a feasibility and usability pilot study . The study was approved by the Regional Ethical Review Board in Lund (Dnr 2016/169) and followed the ethical principles for medical research involving human subjects per the World Medical Association Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study is part of SRIIPSS, which is a prospective (1‐year) longitudinal study of self‐reported SRIIPS . The eHealth application used for data collection has previously been described and tested in a feasibility and usability pilot study . The study was approved by the Regional Ethical Review Board in Lund (Dnr 2016/169) and followed the ethical principles for medical research involving human subjects per the World Medical Association Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…19 The overall objective is to prospectively estimate the burden of SRIIPS among Swedish Paralympic athletes using an eHealth application specifically developed for Paralympic athletes. 20 At the start of this prospective study, the athletes completed a baseline questionnaire on existing and previous SRIIPS during the past year, as well as athlete demographics, impairment, behaviors, and sport characteristics. This allowed us to analyze the prevalence of SRIIPS as an overall indicator of disease status by measuring the proportion of the outcome in this understudied population at different time points.…”
Section: Pm R 12 (2020) 271-280mentioning
confidence: 99%
See 2 more Smart Citations
“…The finding that mHSM usability was associated with the structure of the survey items can be compared to experiences from electronic data collection on pre-participation health in association with athletics championships [26] and mHSM among Paralympic athletes [27]. In both these contexts, the athletes encountered few usability problems, but expressed concerns about medical terminology and formulation of the survey items.…”
Section: Usability Issuesmentioning
confidence: 99%